2012
DOI: 10.1039/c2jm30257h
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of dextran-coated superparamagnetic iron oxide nanoparticles in a capillary-based droplet reactor

Abstract: We describe the controlled synthesis of dextran-coated superparamagnetic iron oxide nanoparticles (SPIONs) using a stable passively-driven capillary-based droplet reactor. High quality highly crystalline particles were obtained with a narrow size distribution of mean diameter 3.6 nm and standard deviation 0.8 nm. The particles were evaluated for use in MRI, and found to exhibit a large saturation magnetisation of 58 emu/g and a high T 2 relaxivity of 66 mM À1 s À1 at 4.7 T, signifying good MRI contrast enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 37 publications
1
93
0
Order By: Relevance
“…Hence, in addition to removing weakly bound dextran more efficiently, SEC leads to a stronger coordination between remaining dextran molecules and the IONC surfaces. 49 It should also be emphasized that the peak at 1043 cm −1 becomes predominant compared to the one at 1020 cm −1 , which is not the case for D-IONCs or dextran alone. In the literature, the weak bands near 1040 and 1020 cm −1 have been correlated to the crystalline (more ordered) and amorphous (less ordered) phases of dextran, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Hence, in addition to removing weakly bound dextran more efficiently, SEC leads to a stronger coordination between remaining dextran molecules and the IONC surfaces. 49 It should also be emphasized that the peak at 1043 cm −1 becomes predominant compared to the one at 1020 cm −1 , which is not the case for D-IONCs or dextran alone. In the literature, the weak bands near 1040 and 1020 cm −1 have been correlated to the crystalline (more ordered) and amorphous (less ordered) phases of dextran, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The superparamagnetic character of the nanoparticles is confirmed by the absence of hysteresis in the magnetization curve. Similar strategy based on droplet microfluidics has been reported by Kumar et al [41] by using a driven capillary-based droplet reactor for the aqueous preparation of dextran-coated superparamagnetic iron oxide nanoparticles. The reactor yielded small, stable, highly crystalline particles with a narrow size distribution ( d /d = 22%), a large saturation magnetization of 58 emu g −1 , and a high T2 relaxivity of 66 mM −1 s −1 .…”
Section: Synthesis Of -Fe 2 O 3 Nanoparticles In Microfluidic Reactorsmentioning
confidence: 93%
“…Later in 2012, Kumar et al [233] reported a simpler passive methodology for direct synthesis of dextran-coated superparamagnetic iron oxide nanoparticles in a capillary-based droplet reactor where droplets are formed close to the end of a length of silicone tubing at the contact point between two auxiliary capillaries. Compared to Frenz et al method, [232] there was no need for the surface modification of the channel and high voltage power sources.…”
Section: Droplet-based Microreactorsmentioning
confidence: 99%